Machine learning for lithology identification in electrical image logging: A case study of the Chang 73 Sub-Member, Yanchang Formation, East Gansu region, Ordos Basin - Jiaqi Li; Hongping Bao; Shilong Liu; Pingping Shi; Feiming Gao; Liubin Wei; Langlang Wang; Hongyan Yu (Earth Science Informatics, 2026)

A guided heterogeneous feature fusion network for real-time prediction of rock strength - Dezhi Sun; Renshu Yang; Jinjing Zuo; Huaqiang liu; Yang Li; Xiaolei Yue (Earth Science Informatics, 2026)

Multi-scale attention sequence networks for lithology identification in the songliao basin - Hao Shi; XiaLin Zhang; ZhangLin Li; Yang Liu; ZhengPing Weng; LiangYu Wang (Earth Science Informatics, 2026)

A multi-dimensional modified deep learning framework for predicting potential creep-type landslides based on geological data - Yue Liu; Peihua Xu; Chen Cao; Liling Jin; Bo Han; Rongchen Ma; Chensi Li (Earth Science Informatics, 2026)

Prior-Driven unsupervised lightweight learning method for seismic signal denoising - Junheng Peng; Xiaowen Wang; Yingtian Liu; Yong Li; Mingwei Wang (Earth Science Informatics, 2026)

HyLiFT: a parameter-efficient hierarchical fusion transformer for imbalanced lithology classification in complex tectonic zones - Yumin Li; Yang Zhang; Yuwei Zu; Ji Li; Binghui Song; Hao Liu (Earth Science Informatics, 2026)

Lithology prediction via multiscale feature-fusion convolutional neural networks - Wenliang Nie; Heyu Zhang; Jiayi Gu; Wei Huang; Bo Li; Jianfeng Liu; Xiangfei Nie (Earth Science Informatics, 2025)

Adaptive ensemble-based malware detection in smart factory IIoT using AERS-WPS algorithm - Lei Liu; Li Guo (Earth Science Informatics, 2025)

Study of 3D geological suitability evaluation via machine learning and gray correlation analysis - Xiaozheng Liu; Peng Zhang; Chang Xu; Dingfei Zhang; Zhaoxuan Dong; Mingjun Li (Earth Science Informatics, 2025)

A method for reconstructing logging curves based on Characterization-enhanced Variational Autoencoder - Xialin Zhang; Jizhen Qu; Zhenjiang Wang; Yang Liu; Zhanglin Li; Liangyu Wang (Earth Science Informatics, 2025)

Predicting offshore downhole rock drillability in complex geological conditions using explainable machine learning and Multi-Source data - Huayang Li; Quanyou Liu; Jiaao Chen; Chi Zhang; Dantong Liu; Zehui Shi; Xinyi Wang (Earth Science Informatics, 2025)

CNN-based transfer learning for self-potential inversion - Yian Cui; Xiangbo Yang; Hao Li; Pu Wang; Jing Xie; Jianxin Liu (Earth Science Informatics, 2025)

An automatic Lithofacies sample labeling method by integrating deep learning and Gaussian mixture model - Zihao Mu; Chunsheng Li; Zongbao Liu; Tao Liu; Kejia Zhang; Haoran Wang; Haiwei Mu; Yuchen Yang (Earth Science Informatics, 2025)

A method for training while drilling to predict electromagnetic wave logging curves based on long short-term memory neural networks - Qiwei Liu; Fanmin Kong; Kang Li (Earth Science Informatics, 2025)

Precise quantitative evaluation of the risk level of coal mine water inrush accidents based on the CW-BN model - Xuezhao Zheng; Yuan Li; Xin Tong; Qingyun Liu (Earth Science Informatics, 2025)

Feasibility of a hybrid AHA-GPR model for predicting blasting fragmention in surface mines - Zhi Yu; Lin-Feng Du; Jian-Xing Liu; Jian Zhou; Chuan-Qi Li (Earth Science Informatics, 2025)

Lithology identification method combining attribute generation group and generative adversarial network - Fengda Zhao; Hongjin Lv; Zhuoyi Zhao; Xianshan Li; Miaomiao Liu (Earth Science Informatics, 2025)

Progress in geothermal gas research in the last 50 years: a bibliometric review - Luyao Wang; Kai Liu; Li Wan; Shouchuan Zhang; Wuhui Jia; Junhan Guo; Tingxi Yu (Earth Science Informatics, 2025)

Segmentation of urban green space and water body based on high-resolution remote sensing images - Chen Yang; Ying Wei; Junwei Liu; Hao Yang; Zhoubang He; Jiaguang Li (Earth Science Informatics, 2025)

A lightweight dual-layer convolutional model for wind power forecasting - Yongsheng Ye; Liu Liu; Yang Li; Xun Liu; Yanlong Xu; Yuchen Liu; Lili Li (Earth Science Informatics, 2025)

Transitional shale reservoir quality evaluation based on Random Forest algorithm—a case study of the Shanxi Formation, eastern Ordos Basin, China - Wanli Gao; Qin Zhang; Jingtao Zhao; Wen Liu; Weiliang Kong; Guangyin Cai; Tianquan Qu; Hongjie Peng; Wenyu Li; Yugang Yang; Yingfang Zhou; Zhen Qiu (Earth Science Informatics, 2025)

Acoustic impedance prediction using an attention-based dual-branch double-inversion network - Wen Feng; Yingtian Liu; Yong Li; Huating Li; Xiaowen Wang (Earth Science Informatics, 2025)

Probabilistic quantile multiple fourier feature network for lake temperature forecasting: incorporating pinball loss for uncertainty estimation - Siyuan Liu; Jiaxin Deng; Jin Yuan; Weide Li; Xi’an Li; Jing Xu; Shaotong Zhang; Jinran Wu; You-Gan Wang (Earth Science Informatics, 2024)
Lake temperature forecasting is crucial for understanding and mitigating climate change impacts on aquatic ecosystems. The meteorological time series data and their relationship have a high degree of complexity and uncertainty, making it difficult to predict lake temperatures. In this study, we propose a novel approach, Probabilistic Quantile Multiple Fourier Feature Network (QMFFNet), for accurate lake temperature prediction in Qinghai Lake. Utilizing only time series data, our model offers practical and efficient forecasting without the need for additional variables. Our approach integrates quantile loss instead of L2-Norm, enabling probabilistic temperature forecasts as probability distributions. This unique feature quantifies uncertainty, aiding decision-making and risk assessment. Extensive experiments demonstrate the method’s superiority over conventional models, enhancing predictive accuracy and providing reliable uncertainty estimates. This makes our approach a powerful tool for climate research and ecological management in lake temperature forecasting. Innovations in probabilistic forecasting and uncertainty estimation contribute to better climate impact understanding and adaptation in Qinghai Lake and global aquatic systems.

A novel secure scheme for remote sensing image transmission: an integrated approach with compression and encoding - Haiyang Shen; Jinqing Li; Xiaoqiang Di; Xusheng Li; Zhenxun Liu; Makram Ibrahim (Earth Science Informatics, 2024)

Precipitation nowcasting leveraging spatial correlation feature extraction and deep spatio-temporal fusion network - Wenbin Yu; Yangsong Li; Cheng Fan; Daoyong Fu; Chengjun Zhang; Yadang Chen; Ming Qian; Jie Liu; Gaoping Liu (Earth Science Informatics, 2024)

A new approach to dividing the tectonic setting of igneous rocks: machine learning and GeoTectAI software - Ming Lei; Wenyan Cai; Xiao Liu; Chao Zhang; Qingyi Cui; Jian Li (Earth Science Informatics, 2024)

A borehole clustering based method for lithological identification using logging data - Hui Liu; XiaLin Zhang; ZhangLin Li; ZhengPing Weng; YunPeng Song (Earth Science Informatics, 2024)

Ultra-short-term photovoltaic power prediction based on modal reconstruction and BiLSTM-CNN-Attention model - Wei Liu; Qian Liu; Yulin Li (Earth Science Informatics, 2024)

Adaptive direct sampling-based approach to ore grade modeling - ZhangLin Li; ShuiHan Yi; Ning Wang; XiaLin Zhang; Qiyu Chen; Gang Liu (Earth Science Informatics, 2024)

Urban building function classification based on multisource geospatial data: a two-stage method combining unsupervised and supervised algorithms - Shouhang Du; Meiyun Zheng; Liyuan Guo; Yuhui Wu; Zijuan Li; Peiyi Liu (Earth Science Informatics, 2024)

Geological structure identification of coalbed methane reservoir based on trend surface and curvature analysis algorithms - Guoxu Chen; Ruirui Li; Li Cao; Fang Lv; Jing Yuan; Panpan Li; Shengdong Liu; Zhongcheng Li (Earth Science Informatics, 2024)

Wildfire susceptibility prediction using a multisource and spatiotemporal cooperative approach - Jiehang Deng; Weiming Wang; Guosheng Gu; Zhiqiang Chen; Jing Liu; Guobo Xie; Shaowei Weng; Lei Ding; Chuan Li (Earth Science Informatics, 2023)

Influence of adaptive inverse distance weighting method under membership function mapping on the interpolation accuracy of geological boreholes - Huan Liu; Weitao Li; Weibo Zeng; Ling Bao; Yuqing Mei; Jing Guo; Lei Cheng; Shuangxi Gu (Earth Science Informatics, 2023)

Impervious surface Mapping and its spatial–temporal evolution analysis in the Yellow River Delta over the last three decades using Google Earth Engine - Jiantao Liu; Yexiang Li; Yan Zhang; Quanlong Feng; Tongguang Shi; Dong Zhang; Pudong Liu (Earth Science Informatics, 2023)

Correction to: Automatic lithology identification method based on efficient deep convolutional network - Yan Guo; Zhuowu Li; Weihua Lin; Ji Zhou; Shixiang Feng; Luyu Zhang; Fujiang Liu (Earth Science Informatics, 2023)

Implementation and verification of a real-time system for automatic aftershock forecasting in China - Zhumei Liu; Haikun Jiang; Shengle Li; Mingxiao Li; Jian Liu; Jingfa Zhang (Earth Science Informatics, 2023)
In this paper, an automatic aftershock forecasting system for China is presented. Based on a parameter-free historical analogy method, this system can produce short-term aftershock forecast, including seismic sequence types and the magnitude of the largest aftershock, within a few minutes after a major earthquake and can further provide scientists and government agencies with a set of background information for consultation purposes. First, the system construction concept and operation framework are described, and an evaluation of the forecast performance of the system is then conducted considering earthquakes from 2019 to 2021 in mainland China. The results indicate that the sequence type classification precision reaches 83.5%, and the magnitude of more than 90% of the aftershocks is smaller than that of upper range forecast. This system is fast and easy to control, and all the reports and maps can be produced approximately 5 min after earthquake occurrence. Practical use verifies that the application of this system has greatly improved the efficiency of post-earthquake consultation in mainland China.

Construction and application of mine water inflow prediction model based on multi-factor weighted regression: Wulunshan Coal Mine case - Bo Li; Huang Wu; Pu Liu; Juan Fan; Tao Li (Earth Science Informatics, 2023)

Automatic lithology identification method based on efficient deep convolutional network - Yan Guo; Zhuowu Li; Weihua Lin; Ji Zhou; Shixiang Feng; Luyu Zhang; Fujiang Liu (Earth Science Informatics, 2023)

Forecasting system with sub-model selection strategy for photovoltaic power output forecasting - Zhenkun Liu; Ping Li; Danxiang Wei; Jianzhou Wang; Lifang Zhang; Xinsong Niu (Earth Science Informatics, 2023)

Knowledge mapping and trends in research on remote sensing change detection using CiteSpace analysis - Yuanhe Yu; Yuzhen Shen; Yaoyao Liu; Yuchun Wei; Xudong Rui; Bingbing Li (Earth Science Informatics, 2023)

Correction to: Non-normal distribution of radon and residual radon and short-term abnormal precursors of residual radon before major earthquakes - Xiaobing Jin; Junwei Bu; Guilan Qiu; Li Ma; Zhongming Chen; Tao Chen; Junwei Wu; Bo Pan; Hai Ji; Jingxuan Tian; Xiaoxiao Wu; Zhipeng Li; et al. (Earth Science Informatics, 2022)

Non-normal distribution of radon and residual radon and short-term abnormal precursors of residual radon before major earthquakes - Xiaobing Jin; Junwei Bu; Guilan Qiu; Li Ma; Zhongming Chen; Tao Chen; Junwei Wu; Bo Pan; Hai Ji; Jingxuan Tian; Xiaoxiao Wu; Zhipeng Li; et al. (Earth Science Informatics, 2022)

Sensitivity analysis of water inrush evaluation model based on the theory of water resistant key strata: a case study in a coal mine, China - Qiang Li; Xiangxi Meng; YuBen Liu (Earth Science Informatics, 2022)

Characterization of seismic information entropy attributes of braided river delta sedimentary microfacies for the upper Shaximiao formation in the Wubaochang area, northeastern Sichuan Basin, China - Yanguo Qiao; Zhigang Liu; Wei Luo; Dianguang Zang; Chenrui Li; Fan Yang; Guoshuai Si (Earth Science Informatics, 2022)

Straw return and organic fertilizers instead of chemical fertilizers on growth, yield and quality of rice - Tingda Wu; Chao Li; Xu Xing; Xipeng Pan; Changhui Liu; Yijing Tian; Ziyu Wang; Junshi Zhao; Jianping Wang; Bing He (Earth Science Informatics, 2022)

Dynamic characteristics of snow frequency and its relationship with climate change on the Tibetan plateau from 2001 to 2015 - Jinbao Liu; Yuting Li; Jing Yu; Yunjun Yao (Earth Science Informatics, 2022)

Research on fish identification in tropical waters under unconstrained environment based on transfer learning - Shan Zhang; Weifang Liu; Yupeng Zhu; Wei Han; Yi Huang; Jianqiang Li (Earth Science Informatics, 2022)
Seafloor unconstrained environment video is shot in uncontrolled open sea area. There are multiple backgrounds, complex illumination and weather changes, and rapid growth of algae and attached lenses, which affect the stability of video shooting quality, resulting in difficulty in image recognition. At present, there is still no algorithm that is superior to other methods generally, and it is necessary to build a model combined with specific scenes and applications. In this paper, a fish identification method in tropical waters based on transfer learning under unconstrained environment is proposed. Firstly, the image is pre-processed by affine transformation to realize data enhancement. Furthermore, RestNet50 deep convolutional neural network is constructed based on transfer learning to compare the effect of fish recognition before and after transfer learning. The results show that, the accuracy and loss indicators are better than those of non-transfer learning when the trained model of imagenet is introduced as the initial weight of the network. When the model is trained to 150 epochs, the indicators begin to converge, which can better complete the fish identification task in tropical waters under unconstrained environment.

Few-shot learning for name entity recognition in geological text based on GeoBERT - Hao Liu; Qinjun Qiu; Liang Wu; Wenjia Li; Bin Wang; Yuan Zhou (Earth Science Informatics, 2022)

Mine inflow prediction model based on unbiased Grey-Markov theory and its application - Bo Li; Huiling Zhang; Yulan Luo; Lei Liu; Teng Li (Earth Science Informatics, 2022)

A novel large-scale land degradation remote sensing index and its application in Three River Source Region - Ye Wen; Qiubing Wang; Bing Guo; Chao Meng; Yumei Cai; Haorun Xue; Huihui Zhao; Wenqian Zang; Cuixia Wei; Yang Yu; Yifeng Liu; Jialin Li (Earth Science Informatics, 2022)

Text visualization for geological hazard documents via text mining and natural language processing - Ying Ma; Zhong Xie; Gang Li; Kai Ma; Zhen Huang; Qinjun Qiu; Hui Liu (Earth Science Informatics, 2022)

A comparative study of threshold selection methods for change detection from very high-resolution remote sensing images - Huaqiao Xing; Linye Zhu; Bingyao Chen; Chang Liu; Jingge Niu; Xuehan Li; Yongyu Feng; Wenbo Fang (Earth Science Informatics, 2022)

Engineering application of fuzzy evaluation based on comprehensive weight in the selection of geophysical prospecting methods - Maoxin Su; Congcong Li; Yiguo Xue; Peng Wang; Kai Cheng; Yimin Liu (Earth Science Informatics, 2022)

Susceptibility assessment of small, shallow and clustered landslide - Xuemei Liu; Pengcheng Su; Yong Li; Jun Zhang; Taiqiang Yang (Earth Science Informatics, 2021)

Method for EMR and AE interference signal identification in coal rock mining based on recurrent neural networks - Yangyang Di; Enyuan Wang; Zhonghui Li; Xiaofei Liu; Baolin Li (Earth Science Informatics, 2021)

Application of improved fuzzy comprehensive evaluation method in karst groundwater quality evaluation: a case study of Cengong county - Wenping Zhang; Bo Li; Zijie Liu; Beibei Zhang (Earth Science Informatics, 2021)

Mapping plant communities within quasi‐circular vegetation patches using tasseled cap brightness, greenness, and topsoil grain size index derived from GF-1 imagery - Qingsheng Liu; Chong Huang; He Li (Earth Science Informatics, 2021)

Fracture recognition in ultrasonic logging images via unsupervised segmentation network - Wei Zhang; Tong Wu; Zhipeng Li; Shiyuan Liu; Ao Qiu; Yanjun Li; Yibing Shi (Earth Science Informatics, 2021)

Attenuation characteristics of ground penetrating radar electromagnetic wave in aeration zone - Shaokang Liu; Zhiping Li; Guizhang Zhao (Earth Science Informatics, 2021)

Research on 3D geological modeling method based on multiple constraints - Ming Hao; Minghui Li; Jianlong Zhang; Yujie Liu; Congjun Huang; Fang Zhou (Earth Science Informatics, 2021)

Joint probability-based classifier based on vine copula method for land use classification of multispectral remote sensing data - Yunlong Zhang; Xuan Wang; Dan Liu; Chunhui Li; Qiang Liu; Yanpeng Cai; Yujun Yi; Zhifeng Yang (Earth Science Informatics, 2020)

Terrace extraction based on remote sensing images and digital elevation model in the loess plateau, China - Lanhua Luo; Fayuan Li; Ziyang Dai; Xue Yang; Wei Liu; Xuan Fang (Earth Science Informatics, 2020)

An overview of satellite remote sensing technology used in China’s environmental protection - Shaohua Zhao; Qiao Wang; Ying Li; Sihan Liu; Zhongting Wang; Li Zhu; Zifeng Wang (Earth Science Informatics, 2017)

Parallel viewshed analysis on a PC cluster system using triple-based irregular partition scheme - Xiao-Dong Song; Guo-An Tang; Xue-Jun Liu; Wan-Feng Dou; Fa-Yuan Li (Earth Science Informatics, 2016)

A new artificial oasis landscape dynamics in semi-arid Hongsipu region with decadal agricultural irrigation development in Ning Xia, China - Danfeng Sun; Xiaoqian Yu; Xiaona Liu; Baoguo Li (Earth Science Informatics, 2016)

Designing sea ice web APIs for ice information services - Xintao Liu; Songnian Li; Wei Huang; Jun Gong (Earth Science Informatics, 2015)

Voltage stability in a long-distance power transmission system impacted by the geoelectric field due to a geomagnetic disturbance - Wei-li Wu; Lian-guang Liu; Chun-ming Liu (Earth Science Informatics, 2014)